Sox17 mediates adult arterial endothelial cell adaptation to hemodynamics. (February 2023) - Kim, Diana; Grath, Alexander; Lu, Yao Wei; Chung, Karl; Winkelman, Max; Schwarz, John J.; Dai, Guohao
Abstract: Sox17 is a critical regulator of arterial identity during early embryonic vascular development. However, its role in adult endothelial cells (ECs) are not fully understood. Sox17 is highly expressed in arterial ECs but not in venous ECs throughout embryonic development to adulthood suggesting that it may play a functional role in adult arteries. Here, we investigated Sox17 mediated phenotypical changes in adult ECs. To precisely control the temporal expression level of Sox17, we designed a tetracycline-inducible lentiviral gene expression system to express Sox17 selectively in cultured venous ECs. We confirmed that Sox17-induced ECs exhibit a gene profile favoring arterial and tip cell identity. Furthermore, in comparison to control ECs, Sox17-activated ECs under shear leads to greater expression of arterial markers and suppression of venous identity. These data suggest that Sox17 enables greater hemodynamic adaptability of ECs in response to fluid shear stress. Here, we also demonstrate key morphogenic behaviors of Sox17-mediated ECs. In both vasculogenic and angiogenic 3D fibrin gel studies, Sox17-mediated ECs prefer to form cohesive vessels with one another while interfering the vessel formation of the control ECs. Sox17-mediated ECs elicit hyper-sprouting behavior in the presence of pericytes but not fibroblasts, suggesting Sox17 mediated sprouting frequency is dependent on supporting cell type. Using a microfluidic chip, we also show that Sox17-mediated ECs maintain thinner diameter vessels that do not widen under interstitial flow like the control ECs. Taken together, these data showed that Sox17 mediated EC gene expression and phenotypical changes are highly modulated in the context of biomechanical stimuli, suggesting Sox17 plays a role in regulating the arterial ECs adaptability under arterial hemodynamics as well as tip cells behavior during angiogenesis and vasculogenesis. The results from this study may be valuable in improving vein graft adaptation to arterial hemodynamics and bioengineering microvasculature for tissue engineering applications.